2014
DOI: 10.1007/s00774-014-0599-1
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy delineates radiation-induced injury and partial rescue by amifostine in bone: a murine mandibular model

Abstract: Despite its therapeutic role in head and neck cancer, radiation administration degrades the biomechanical properties of bone and can lead to pathologic fracture and osteoradionecrosis. Our laboratories have previously demonstrated that prophylactic amifostine administration preserves the biomechanical properties of irradiated bone and that Raman spectroscopy accurately evaluates bone composition ex vivo. As such, we hypothesize that Raman spectroscopy can offer insight into the temporal and mechanical effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
(26 reference statements)
0
15
0
Order By: Relevance
“… 27 Furthermore, amifostine pre-treatment preserved bone mineralization to the level of the nonirradiated control 18 weeks following radiotherapy, as there was no statistical difference between the mineral density levels and mineral to collagen ratios between groups. 27 , 28 These results, corroborated with micro-CT analysis, demonstrated that amifostine prophylaxis maintained mineralization metrics (BVF, BMD, and TMD) of irradiated bone to that of the nonirradiated controls. 24 …”
Section: Pharmaceutical and Cellular-based Therapeuticsmentioning
confidence: 66%
“… 27 Furthermore, amifostine pre-treatment preserved bone mineralization to the level of the nonirradiated control 18 weeks following radiotherapy, as there was no statistical difference between the mineral density levels and mineral to collagen ratios between groups. 27 , 28 These results, corroborated with micro-CT analysis, demonstrated that amifostine prophylaxis maintained mineralization metrics (BVF, BMD, and TMD) of irradiated bone to that of the nonirradiated controls. 24 …”
Section: Pharmaceutical and Cellular-based Therapeuticsmentioning
confidence: 66%
“…This study demonstrated that the depolarization ratios of mineral to collagen were significantly lower in the group that received radiotherapy than in the group that received radiotherapy in conjunction with AMI. Studies using Raman spectroscopy have reported that radiation induces damages to the chemical composition and ultrastructure of bone and prophylaxis with AMI causes a recovery towards the normal, native composition and orientation of the minerals and collagen in bones [46, 47]. In a rat model of radiotherapy with mandibular distraction osteogenesis, the mean bone volume fraction significantly decreased in the group that received radiotherapy alone in comparison to the group that received radiotherapy in conjunction with AMI (0.35 vs. 0.76).…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58][59][60][61] Raman spectroscopy has been successfully employed to both in vivo and in vitro, and one can easily find its application in various fields of medicine including pathology, 62,63 physiology, 64 virology, 65 urology, 66,67 and dentistry. [68][69][70] Either by using cells, dissected tissues or real time monitoring during surgery, researchers have demonstrated the utility of Raman spectroscopy, particularly in cancers related to brain, 71,72 83,84 Additionally, by analyzing biofluids such as blood and urine, non-invasive diagnostic assays are also being actively developed for many diseases such as diabetes (glucose level monitoring), 85,86 cancer, 87,88 asthma, 89 and malaria. 90,91 Most of these studies relied on univariate analysis (one or two marker bands used for biomolecular identification).…”
Section: Medical Applicationsmentioning
confidence: 99%